SENSITIVE ELEMENTS FOR CAPACITOR SENSORS OF ACCELERATION - N. I. Mukhurov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In article variants of designs of sensitive elements for capacitor sensors of acceleration in plane-parallel and volumetric structure are offered. By results of the analysis of functional characteristics the range of sensitivity of sensors is established depending on design parameters.